(untitled) - Das, Braja M. (Mason, OH, 2010)
Principles of geotechnical engineering offers an overview of soil properties and mechanics together with coverage of field practices and basic engineering procedure. Principles of geotechnical engineering contains more figures and worked out problems than any other text on the market and provides the background information needed to support study in later design-oriented courses or in professional practice.
Keywords: Soil mechanics,Geotechnical engineering,Cơ học đất,Địa kỹ thuật